Mechanism of separation and removal of water from dewatered sludge using L-DME to dissolve hydrophilic organic matter. (May 2020) - Chen, Le; Zhu, Wei; Lin, Nai-Xi; Mu, Biao; Fan, Xi-Hui; Wang, Chen-Yu; Chen, Huai-Min; Zhong, Jun
Abstract: Difficulties in advanced dewatering of dewatered sludge hinder sludge reduction and resource utilization. L-DME (liquified dimethyl ether) has been recently used for dewatering, but the effect of organic matter dissolution using L-DME during desorption and dehydration on water removal is not clear. In this study, dewatered sludge from urban sewage treatment plants was used to conduct experiments in sequencing dissolution-separation reactors. The changes in the dehydration rate, bound water and various organic matter levels at different times, L-DME additions, and the temperature were measured. The results show that L-DME can remove 90% of water, 100% of lipids, and 8–12% of organic matter in dewatered sludge. L-DME was mixed with the semi-like colloidal sludge, and high separation of water was achieved by mixing the L-DME with water and dissolving the hydrophilic organic matter to convert the solid-like into a two-phase (solid and liquid) substance, which can be easily separated. The dissolution of hydrophilic organic matter such as polysaccharides and proteins by L-DME promotes the conversion of bound water into free water, which is key to total water removal. Graphical abstract: Image 1 Highlights: Advanced dewatering experiments were conducted using L-DME for dewatered sludge. Changes in organic matter content of dewatered sludge after L-DME dissolution were studied. L-DME removed 90% of water, 100% of lipids, and 8–12% of organic matter in dewatered sludge. The dissolution of L-DME to hydrophilic organic matter is the key of moisture removal. Combined water in dewatered sludge became a free liquid easily separated from the particulate matter.